Public transport governance in the Netherlands: More recent developments. (November 2016) - Veeneman, Wijnand
Abstract: Like in the 2013 version of this paper, it recaps the latest developments in the governance of public transport in the Netherlands, focusing on bus, tram, metro and train concessions. Most of the concessions are competitively tendered, since the introduction of a legal obligation to tender in 2001. Dutch public transport authorities have since chosen a variety of concession setups and forms of contract remuneration. This variety has remained large in terms of ways of tendering, but in addition, the three major cities were allowed in 2012 to choose not to tender out their concessions. This paper again explores that variety and describes recent changes at the national and regional levels from 2013 onwards and looks at the developments that were first coming up in 2012. The paper describes key trends and lessons from the Dutch experience based on a nine-year project drawing lessons on competitive tendering with authorities, operators and consultants, and based on interviews with representative of 13 of the 14 public transport authorities. Key trends are a national focus on rail transport, dealing with austerity measures, implementing the earlier push for defragmentation by the national government, tweaking of the governance and preparing for bigger changes that might have major impacts on the markets for public transport. Finally, the article presents a four phase model of implementation of governance changes after in the introduction of competitive tendering in 2001.